Meykaṇṭārum civañāṉapōtamum - Cuppiramaṇiya Piḷḷai, Kā., 1888-1945 (SAMP early 20th-century Indian books project, 1949)
Study of the life of Meykaṇṭatēvar, Tamil religious poet, and his work Civañāṉapōtam, verse work on the Saivasiddhanta school of Hindu philosophy.